Optimization of Engineered Production of the Glucoraphanin Precursor Dihomomethionine in Nicotiana benthamiana - Crocoll, Christoph; Mirza, Nadia; Reichelt, Michael; Gershenzon, Jonathan; Halkier, Barbara Ann (Frontiers in Bioengineering and Biotechnology, 2016)
Glucosinolates are natural products characteristic of the Brassicales order which include vegetables such as cabbages and the model plant Arabidopsis thaliana. Glucoraphanin is the major glucosinolate in broccoli and associated with the health-promoting effects of broccoli consumption. Towards our goal of creating a rich source of glucoraphanin for dietary supplements, we have previously reported the feasibility of engineering glucoraphanin in Nicotiana benthaminana through transient expression of glucoraphanin biosynthetic genes from Arabidopsis thaliana (Mikkelsen et al., 2010). As side-products, we obtained 5-8 fold higher levels of chain-elongated leucine-derived glucosinolates, not found in the native plant. Here, we investigated two different strategies to improve engineering of the methionine chain elongation part of the glucoraphanin pathway in N. benthamiana: 1) co-expression of the large subunit (LSU1) of the heterodimeric isopropylmalate isomerase, and 2) co-expression of BAT5 transporter for efficient transfer of intermediates across the chloroplast membrane. We succeeded in raising dihomo-methionine (DHM) levels to a maximum of 432 nmol*g-1 fresh weight which is equivalent to a 9-fold increase compared to the highest production of this intermediate previously reported (Mikkelsen et al., 2010). The increased DHM production without increasing leucine-derived side-product levels provides new metabolic engineering strategies for improved glucoraphanin production in a heterologous host.